No correlation between NF1 mutation position and risk of optic pathway glioma in 77 unrelated NF1 patients - Hutter, Sonja; Witt, Olaf; Pfister, Stefan (Human genetics, 2016)
Neurofibromatosis type 1 (NF1) is a common monogenic disorder whereby affected individuals are predisposed to developing CNS tumors, including optic pathway gliomas (OPGs, occurring in ~15 to 20 % of cases). So far, no definite genotype-phenotype correlation determining NF1 patients at risk for tumor formation has been described, although enrichment for mutations in the 5′ region of the NF1 gene in OPG patients has been suggested. We used whole exome sequencing, targeted sequencing, and copy number analysis to screen 77 unrelated NF1 patients with (n = 41) or without (n = 36; age ≥10 years) optic pathway glioma for germline NF1 alterations. We identified germline NF1 mutations in 69 of 77 patients (90 %), but no genotype-phenotype correlation was observed. Our data using a larger patient cohort did not confirm the previously reported clustering of mutations in the 5′ region of the NF1 gene in patients with OPG. Thus, NF1 mutation location should not currently be used as a clinical criterion to assess the risk of developing OPGs.
Im Titel ist "NF1" in NF1 mutation kursiv geschrieben
Gesehen am 22.10.2019